Metabolic Syndrome and Cognitive Decline - Yaffe, Kristine (Current Alzheimer Research, 2007)
Over 33% of women and 20% of men aged 65 and older will develop dementia during their lifetime, and many more will develop a milder form of cognitive impairment. Given the anticipated exponential increase in both the incidence and prevalence of cognitive impairment in the next century, it is critical to identify preventative strategies to thwart this critical public health issue. The metabolic syndrome is comprised of five cardiovascular risk factors that include abdominal obesity, hypertriglyceridemia, low high density lipoprotein (HDL) levels, hypertension, and hyperglycemia. The prevalence of the metabolic syndrome, similar to that for cognitive disorders, increases dramatically with age. While several of the individual components of the metabolic syndrome have been linked to risk of developing dementia and cognitive impairment, few studies have looked at the components of the metabolic syndrome as a whole. We found, in two separate studies involving elders of different ethnicities, that the metabolic syndrome is a risk factor for accelerated cognitive aging. This was especially true for elders with the metabolic syndrome and with elevated serum level of inflammation. Several possible mechanisms may explain the association between the metabolic syndrome and cognitive decline including micro- and macro-vascular disease, inflammation, adiposity and insulin resistance. If metabolic syndrome is associated with increased risk of developing cognitive impairment, regardless of mechanism, then early identification and treatment of these individuals might offer avenues for disease course modification.
Keywords: dementia